(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study analyzes the role of Artificial Intelligence (AI) governance in enhancing digital privacy and fostering ethical trust within the context of digital marketing in the Kingdom of Saudi Arabia, by examining the degree to which governance requirements and indicators are embedded in relevant national regulatory frameworks. A descriptive-analytical approach based on documentary content analysis was adopted. A purposive sample of four key national documents was analyzed: the Personal Data Protection Law (PDPL, 2021), its Executive Regulations (2023), the AI Ethics Principles issued by the Saudi Data and Artificial Intelligence Authority (SDAIA, 2023), and the Data Cybersecurity Controls (DCC-1:2022). A structured coding instrument was developed using operational indicators aligned with the study’s four analytical axes, and a three-point scale (0/1/2) was applied to the selected units of analysis. The findings reveal noticeable variation in the degree of governance inclusion across the analyzed documents, with an overall average of approximately 60.9%, indicating a moderate to relatively high level of regulatory readiness. The PDPL and its Executive Regulations achieved the highest scores in terms of privacy protection and individual rights, whereas SDAIA’s principles emphasized value-based dimensions such as transparency and explainability. In contrast, DCC-1 demonstrated strong technical provisions for data security but comparatively weaker coverage of transparency and individual rights. Overall, and within the limits of documentary inference, the results suggest that the Saudi regulatory ecosystem provides a solid legal and ethical foundation for AI governance, while still requiring stronger operational requirements related to algorithmic transparency, objection mechanisms, and explicit marketing-related applications.